L1 acquisition and L2 learning : the view from Romance - Avram, Larisa; Sevcenco, Anca; Tomescu, Veronica (Language acquisition & language disorders, 2021)
"This volume includes fourteen papers on the acquisition of Romance languages, eleven of which were presented at the Romance Turn 9, held in Bucharest in September 2018. The studies offer new insights into central issues in the literature, such as syntactic complexity in both typical and impaired language settings, intervention effects, the acquisition of phenomena which involve both syntactic parameters and an external interface, as well as cross-linguistic interference effects. They present novel longitudinal and experimental data on the first language acquisition and second language learning of French, Italian, European and Brazilian Portuguese, Romanian and Spanish. A unique feature of this volume is the focus on the interaction of language specific properties and of factors which are not specific to the faculty of language in the narrow sense, such as data processing, the nature of the input, discourse structure, computational load, sociolinguistic properties, and the development of Theory of Mind"--